Treatment of unicameral bone cyst: Systematic review and meta analysis. (March 2014) - Kadhim, Muayad; Thacker, Mihir; Kadhim, Amjed; Holmes, Laurens
Purpose: Different treatment modalities have been utilized to treat unicameral bone cyst (UBC), but evidence has not been fully described to support one treatment over another and the optimal treatment is controversial. The aim of this quantitative systematic review was to assess the effectiveness of different UBC treatment modalities. Methods: We utilized Pubmed to isolate retrospective studies on patients with UBC who received any kind of treatment. The included studies needed to have a minimum sample size of 15 patients, and have provided data on radiographic healing outcome. Results: Sixty-two articles were selected for the meta-analysis from a total of 463 articles. The cumulative sample size was 3, 211 patients with 3, 217 UBC, and male to female ratio was 2.2:1. The summary or pool estimate of methylprednisolone acetate (MPA) injection resulted in a healing rate of (77.4 %) that was comparable to bone marrow injection (77.9 %). A higher healing rate was observed with MPA injection when inner wall disruption was performed. The pool estimate of bone marrow with demineralized bone matrix injection was high (98.7 %). UBC healing rate after surgical curettage was comparable whether autograft or allograft was utilized (90 %). UBC treatment with flexible intramedullary nails without curettage provided almost 100% healing rate, while continuous decompression with cannulated screws provided 89 % healing rate. Conservative treatment indicated a healing rate of 64.2, 95 % CI (26.7–101.8). Conclusions: Active treatment for UBC provided variable healing rates and the outcomes were favorable relative to conservative treatment. Due to the heterogeneity of the studies and reporting bias, the interpretation of these findings should be handled with caution.